2012
DOI: 10.1371/journal.pone.0049850
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Studies Support the Potential for Iatrogenic Transmission of Variant Creutzfeldt Jakob Disease through Dental Procedures

Abstract: BackgroundEvidence is required to quantify the potential risks of transmission of variant Creutzfeldt Jakob (vCJD) through dental procedures. Studies, using animal models relevant to vCJD, were performed to address two questions. Firstly, whether oral tissues could become infectious following dietary exposure to BSE? Secondly, would a vCJD-contaminated dental instrument be able to transmit disease to another patient?MethodsBSE-301V was used as a clinically relevant model for vCJD. VM-mice were challenged by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The potential risk of further human-to-human transmission of the disease through contaminated instruments is a further concern 64 . Recently, a study in the UK indicated that the risk of vCJD transmission during oral health-care procedures was higher than previously expected 111 . This study also revealed transmission of vCJD after exposure of a patient's gingival tissues to a contaminated endodontic file, and not just from nerve tissue exposure, as previously suggested.…”
Section: Creutzfeldt-jakob and Other Prion Diseasesmentioning
confidence: 85%
“…The potential risk of further human-to-human transmission of the disease through contaminated instruments is a further concern 64 . Recently, a study in the UK indicated that the risk of vCJD transmission during oral health-care procedures was higher than previously expected 111 . This study also revealed transmission of vCJD after exposure of a patient's gingival tissues to a contaminated endodontic file, and not just from nerve tissue exposure, as previously suggested.…”
Section: Creutzfeldt-jakob and Other Prion Diseasesmentioning
confidence: 85%
“…• • Difficulty in adequately cleaning endodontic files (Walker et al, 2007); • • The risk of transmission of infectious diseases (Laheij et al, 2001); • • The potential transmission of prion disease (Kirby et al, 2012;Walker et al, 2007);…”
Section: Introductionmentioning
confidence: 99%
“…Drivers to recent improvements were the identification of poor performance (including quantities of residual protein on instruments ready for re-use [1][2][3][4] ) and the risk assessments undertaken to determine potential for transmission of iatrogenic CJD via surgical routes. 5,6 The scientific principles underpinning the cleaning and sterilisation of surgical instruments has been understood for several decades. Unfortunately, many of these reports [7][8][9] are now frequently overlooked by those new to the field.…”
mentioning
confidence: 99%